WAYS OF IMPROVEMENT OF RESULTS PLASTIC OPERATIONS ON THE ABDOMINAL WALL - Малик, С.В.; Drabovskiy, V.S. (World of Medicine and Biology, 2016)
In the article an analysis and review of information of literature is resulted on issue of treatment of patients slipshod and by deformations of front abdominal wall. The types of operative interferences are thoroughly considered at this pathology, resulted ways improvements of technical, diagnostic medical aspects, described popular complications after operation.